SOLAR VEHICLES FROM ENVIRONMENTAL LAW PERSPECTIVE - Tjahjani, Joejoen; Nahdliyah, Hadziqotun; Dwi Erarti, Dinda Ayu (Jurnal Independent, 2022)
ABSTRACT Solar powered vehicles are important as a form of protection for the environment, apart from being a solution to the problem of vehicle exhaust pollution, they are also an innovation in the use of environmentally friendly new and renewable energy (EBT). The use of solar power in vehicles from an environmental law perspective still requires consistency and legal certainty so that there is a clearer footing for investors, as well as the ability to compete with other countries, as expected in the EBT Bill.